Explaining the high number of infected people by dengue in Rio de Janeiro in 2008 using a susceptible-infective-recovered model - Botari, Tiago [UNESP]; Alves, S. G.; Leonel, Edson Denis [UNESP] (Amer Physical Soc, 2011)
An epidemiological model for dengue propagation using cellular automata is constructed. Dependence on temperature and rainfall index are taken into account. Numerical results fit pretty well with the registered cases of dengue for the city of Rio de Janeiro for the period from 2006 to 2008. In particular, our approach explains very well an abnormally high number of cases registered in 2008. A phase transition from endemic to epidemic regimes is discussed.